Analisis Penerapan Kurikulum 2013 dalam Meningkatkan Prestasi Belajar Siswa di MTs Al Ittihadiyah Laut Dendang - Neliwati, Neliwati; Harahap, Halimatussakdiah; Marpaung, Khairun Nisa; Harahap, Nur Fauziah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The implementation of the 2013 curriculum requires teachers to professionally design effective and meaningful (fun) learning, organize learning, choose the right approach, determine learning procedures and build competence effectively, and set success criteria. In implementing the 2013 Curriculum, learning achievement can be integrated into all learning in every field of study contained in the curriculum. This makes teachers who have used traditional evaluations have to change their evaluations, namely to become authentic evaluations based on curriculum demands. In accordance with the problem, this study aims to analyze